AN URGENT NEUROLOGY CONSULT FOR SHORTNESS OF BREATH. Issue 10 (9th September 2014) - Rudd, Daniel; Ming, Caroline; Powell, Natalie; Zhang, Liqun
Abstract : A 40 year old previously fit man presented directly from the airport on his return from a holiday with a two week history of progressive dyspnoea. Three months prior, he had acute onset severe left shoulder pain and rapid progressive weakness. Examination revealed marked atrophy of the left deltoid, triceps and supraspinatus, and limited shoulder adduction. Vital Capacity (VC) was 2.3 L on standing, falling to 0.45 L when supine. CXR was reported as poor inspiratory effort. EMG demonstrated denervation of the C5/C6 muscle group and bilateral phrenic nerve palsy. He was treated with intravenous methylprednisolone followed by oral steroids. He required nocturnal CPAP during sleep. Four months later, his VC improved to 3.09L sitting and 1.03 L supine with full range of shoulder adduction. He continued nocturnal CPAP and physiotherapy, and returned to his full time job. Phrenic nerve involvement has been reported in up to 5% of cases of brachial neuritis, bilateral involvement is rare. It has a prolonged recovery course. This case highlights the need for clinicians to be aware of this rare complication of brachial neuritis. We discuss the assessment and treatment of diaphragmatic dysfunction due to phrenic nerve palsy and review the literature.